Web-Based Customer Relationship Management (CRM) System At Enc Audio to Improve Customer Satisfaction - Khairun Nisa; Dewi Maharani; Santoso Santoso (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
This study aims to design and develop a web-based Customer Relationship Management (CRM) information system at ENC AUDIO, a business engaged in musical instrument and sound system rental services, in order to improve customer satisfaction and service quality. The main problem faced is that customer data, transaction records, and rental schedules are still managed manually, which often leads to data recording errors, scheduling conflicts, difficulties in tracking customer history, and inefficiencies in service processes. The research method used is the Operational CRM approach, with data collection techniques including observation, interviews, and documentation. The system is developed using the CodeIgniter framework and MySQL database, while system testing is conducted using the black box testing method to ensure that all system functions operate properly according to user requirements. The results of this study indicate that the developed CRM system is able to automate customer service processes, manage booking schedules in real time, and store customer transaction history in a structured and integrated manner. In addition, features such as online booking, automated scheduling, and live chat significantly enhance communication between customers and administrators. Therefore, the implementation of this system improves operational efficiency, reduces errors, and strengthens customer relationships, ultimately contributing to increased customer satisfaction and business sustainability.